Fractionation of Plasminogen by Starch Gel Electrophoresis - Slotta, Karl H.; Gonzalez, J. D (Thrombosis and Haemostasis, 1964)
When urea or ε-amino caproic acid were used as solublizing agents for plasminogen in electrophoretic experiments, only one broad band of the proenzyme was obtained on acetate cellulose, in starch block, and in acrylamide gel. In starch gel electrophoresis, however, both forms of plasminogen – the native or euglobulin and Kline’s or Pseudoglobulin plasminogen – separated into six bands. These migrated toward the cathode at room temperature in borate or veronal buffer in the alkaline range and showed full activity in fibrinagar-streptokinase plates.